2014
DOI: 10.1007/s00280-014-2588-4
|View full text |Cite
|
Sign up to set email alerts
|

Significant association of combination of OCT4, NANOG, and SOX2 gene polymorphisms in susceptibility and response to treatment in North Indian breast cancer patients

Abstract: Combination of genetic variants of ESCs gene may have a profound effect in breast cancer risk and response to NACT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
(74 reference statements)
1
11
0
Order By: Relevance
“…In India, the mean age of BC diagnosis was 53 years (Tulsyan et al, 2014), and the median age was 45 years (Krishnatreya et al, 2014). This was similar to data from China, which indicated that the estimated risk of recurrent breast cancer increased with age (mean=46 years) .…”
Section: Non-modifiable Risk Factors For Breast Cancer In Asia Agesupporting
confidence: 78%
See 3 more Smart Citations
“…In India, the mean age of BC diagnosis was 53 years (Tulsyan et al, 2014), and the median age was 45 years (Krishnatreya et al, 2014). This was similar to data from China, which indicated that the estimated risk of recurrent breast cancer increased with age (mean=46 years) .…”
Section: Non-modifiable Risk Factors For Breast Cancer In Asia Agesupporting
confidence: 78%
“…BRCA1, ERCC1, TP53) (Chen et al, 2013a;Liu et al, 2013b;Pei et al, 2014;Sun et al, 2014a;Fu et al, 2015;Haryono et al, 2015;Wu et al, 2015), transcription factors (e.g. CDX2, TBX21) (Tulsyan et al, 2014;Yu et al, 2014;Iqbal et al, 2015), estrogen-related enzymes or receptors (e.g. CYP1A2, CYP19A1, ESR1) (Son et al, 2015;Sun et al, 2015b) and cell surface glycoproteins, growth factors or their receptors (e.g.…”
Section: Vietnammentioning
confidence: 99%
See 2 more Smart Citations
“…Other researchers also have found that Lin28-induced chemotherapy resistance is associated with let-7, Rb, p21 and Bcl-xL, thus unraveling complicated relationship between Lin28 and tumor resistance [61, 62]. As for clinical study, by evaluating the polymorphism of Lin28 gene between breast cancer females and healthy controls, researchers have found that genetic variations in Lin28 might be a possible mechanism underlying susceptibility and clinical features in breast cancer, including the response to neoadjuvant chemotherapy [63]. …”
Section: Multiple Processes Regulated By Lin28 In Breast Cancermentioning
confidence: 99%